The Effect of Curriculum Selection on Developmentally Appropriate Practice and Kindergarten Readiness in Prekindergarten - Tilley, Jennifer (Southwest Baptist University, 2019)
As federal mandates such as No Child Left Behind and Race to the Top have created educational reform movements, whose impacts can be seen with increasing accountability pressures in the K-12 world, a greater focus is being placed on early childhood education. It is often felt by proponents of DAP that standards for Early Childhood are developed with a focus on the end product of desired results, without consideration to the developmental nature of children at this age. The researcher sought to understand if the CCSS-ELA Standards are developmentally appropriate for Prekindergarten and Kindergarten students as revealed by individual students’ KELI-4 scores. The literature review included the following themes in the literature: developmental learning theories, theoretical frameworks, play, developmentally appropriate practice, whole child approach, early literacy development, brain research, stages of development, and standards and curriculum shift. In the theoretical framework section, information is presented about these very important contributors to the field of education and specifically early childhood education: John Dewey, Lev Vygotsky, Jean Piaget, Maria Montessori, and Jerome Bruner. Schools with state-funded Prekindergarten programs from across the state of Kansas were included in the research. Once the sample of schools had been identified, their kindergarten readiness assessment results for the spring of 2016 and 2017 and the fall of 2016 and 2017 were collected. Statistical analysis was performed using the SPSS program. Data was analyzed using an independent sample two-tailed t test.